Análise da relação entre pagamentos eletrônicos e crescimento econômico nos países do BRICS e G7 - Sena, Breno Cesar de (Universidade Federal de São Carlos, 2024)
This study examines the impact of electronic payments on economic growth in BRICS and G7 countries during the period from 2012 to 2021. The results show a positive and significant relationship between the use of electronic payments and economic growth. Both cards and cashless payments were associated with a positive stimulus to economic growth, while payment terminals showed a slowing effect on the economy. These findings highlight the importance of electronic payments as drivers of economic growth and promoters of financial inclusion, by facilitating access to financial services for a broader segment of the population. However, it is important to consider the specificities of each country and economic group. As a policy suggestion, countries are encouraged to promote initiatives that encourage the adoption and use of electronic payments, aiming to reduce transaction costs, improve the efficiency of financial operations, and increase transparency and tax revenue collection, reducing tax evasion. Furthermore, it is essential for governments to work in collaboration with the private sector and other stakeholders to implement comprehensive policies that stimulate the culture of using electronic payments by a large segment of the population. By doing so, countries can reap the benefits of the digital economy and promote financial inclusion, contributing to a virtuous cycle of sustainable economic growth.
Analysis of the relationship between electronic payments and economic growth in BRICS and G7 countries
Análisis de la relación entre pagos electrónicos y crecimiento económico en los países BRICS y G7
Keywords: Pagamentos eletrônicos; Crescimento econômico; Inclusão financeira; Electronic payments; Economic growth; Financial inclusion; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO